BIOSORPSI KROMIUM(VI) PADA SERAT SABUT KELAPA HIJAU (Cocos nucifera) - I Wayan Sudiarta; Dwi Ariani Yulihastuti (Jurnal Kimia (Journal of Chemistry), 2010)
Studies on biosorption of chromium (VI) on green coconut coir fibre (Cocos nucifera) biosorbent have beencarried out. These studies included determination of biosorben acidity, optimum pH, contact time of biosorption,isoterm and biosorption capacity, and interaction type between chromium (VI) and green coconut coir fibre (Cocosnucifera) biosorben Mechanisms of interaction were determined through study on desorption chromium (VI) of thepreviously adsorbed using aquadest, 1 M HCl and 0,05 M Na2EDTA.The result showed that the total acidity of green coconut coir fibre biosorbent was 8,7158 ± 0,2569 mmol/g,the optimum pH was 2, and the contact time was 120 minute. Biosorption capacity of green coconut coir fibre (Cocosnucifera) to chromium (VI) was 12,6152 mg/g. Interaction type that occurred between chromium (VI) ion and greencoconut coir fibre biosorben (Cocos nucifera) were hydrogen bond, Van der Walls bond, cation exchange andcomplex bond.